Evaluation of Health-Related Quality of Life in Children and Adolescents with Familial Mediterranean Fever - Durcan, Gizem; Barut, Kenan; Haslak, Fatih; Yıldız, Mehmet; Kadak, M. Tayyib; Adrovic, Amra; Şahin, Sezgin; Doğangün, Burak; Kasapçopur, Özgür (Cerrahpaşa Medical Journal, 2021)
Objective: Health-related quality of life (HRQOL) is a concept that assesses the effects of physical symptoms, functional status, and current illness on psychological and social functioning. In this study, we aimed to examine the quality of life in children and adolescents with familial Mediterranean fever (FMF) according to personal and disease-related factors. Methods: A total of 257 children and adolescents with FMF aged 8–18 years were included in the study. The Juvenile Auto-inflammatory Disease Multidimensional Assessment Report was used for assessment of functional ability (self-report scale), pain (visual analog scale - VAS), therapeutic compliance, and HRQOL (physical, social, school, and emotional status). An increase in all subscale scores indicated a worsening. Results: The mean age of the patients was 12.4±2.63 years, and 132 (51.4%) of them were women. In adolescents, HRQOL-general, -social, -school, and -emotional scores were higher than children (p<0.001 for all). Also, all HRQOL subscale scores of females were significantly higher than males (p<0.05 for all). Patients who had an attack in the last month had higher functional ability, pain, and all HRQOL subscale scores. However, patients with and without exertional leg pain had similar results in terms of all HRQOL subscales. The VAS pain score was positively correlated with HRQOL-general, -physical, -school, and -emotional scores. The therapeutic compliance scores were positively weakly correlated with all HRQOL subscales other than HRQOL-physical. Conclusion: This study showed that the quality of life was worse in the adolescent age group, female gender, and the presence of attacks. Cite this article as: Durcan G, Barut K, Haslak F, Yıldız M, Kadak MT, Adrovic A, et al. Evaluation of Health-Related Quality of Life in Children and Adolescents with Familial Mediterranean Fever. Cerrahpaşa Med J 2021; 45(1): 21-27.